2009
DOI: 10.1115/1.3089536
|View full text |Cite
|
Sign up to set email alerts
|

RANS Analyses of Turbofan Nozzles With Internal Wedge Deflectors for Noise Reduction

Abstract: Computational fluid dynamics (CFD) was used to evaluate the flow field and thrust performance of a promising concept for reducing the noise at take-off of dual-stream turbofan nozzles. The concept, offset stream technology, reduces the jet noise observed on the ground by diverting (offsetting) a portion of the fan flow below the core flow, thickening and lengthening this layer between the high-velocity core flow and the ground observers. In this study a wedge placed in the internal fan stream is used as the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The secondary nozzle can be tailored to induce asymmetry in the plume, at azimuthal directions where noise reduction is desired. Inducing asymmetry in the plume entails either geometrically offsetting the nozzle ducts 3,13,14 , or installing devices that deflect the bypass stream 13,15,16,17 . The misalignment between the primary and secondary streams produces a thick, lowspeed layer, that is oriented typically at downward and sideline azimuthal directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary nozzle can be tailored to induce asymmetry in the plume, at azimuthal directions where noise reduction is desired. Inducing asymmetry in the plume entails either geometrically offsetting the nozzle ducts 3,13,14 , or installing devices that deflect the bypass stream 13,15,16,17 . The misalignment between the primary and secondary streams produces a thick, lowspeed layer, that is oriented typically at downward and sideline azimuthal directions.…”
Section: Introductionmentioning
confidence: 99%
“…The enlarged secondary core reduces the convective Mach number of the primary eddies that radiate sound in the directions of the thickened coannular flow 14 . The addition of a third (tertiary) stream opens a parameter space to explore noise reduction technologies using the aforementioned methods [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Asymmetry in the nozzle entails offsetting the primary and secondary ducts, while asymmetry in the jet plume (issuing from a coaxial arrangement) can be induced by placing deflectors in the secondary stream. These "offset stream" approaches have been investigated for supersonic [13][14][15][16][17] and subsonic [16][17][18][19] jets. The acoustic benefit at supersonic speed can be substantial, while it is more moderate at subsonic speed.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Experiments and computations have revealed that the deflectors reduce the downward turbulent kinetic energy (TKE) but can also introduce a localized increase in the upward TKE. [3][4][5][6] Recent work has shown a correlation between the reduction in downward TKE and the reduction in downward peak overall sound pressure level. 7 The wedge-shaped deflector is an intriguing device with strong potential benefits but requiring great care in its design.…”
Section: Introductionmentioning
confidence: 99%